Pengembangan Media Video Animasi Berbasis Kearifan Lokal pada Materi Keberagaman Makhluk Hidup di Lingkunganku Siswa Sekolah Dasar Kelas IV - Anisah Gultom; Febrianti Yuli Satriyani (BASICA, 2023)
Learning Natural Sciences (IPA) on the diversity of living things in an elementary school environment is learning that can develop logical, rational, systematic and critical thinking skills through the development of the concept of the diversity of living things in the environment. Students can build meaning from the messages generated in communication on learning activities, such as oral, written, graphic. However, learning Natural Sciences (IPA) is still very difficult for elementary school students to understand, this is a concept because Natural Sciences (IPA) is still abstract. it is still difficult to understand the explanation of the material from "Diversity of Living Things in the Environment". This study aims to provide learning media for Natural Sciences (IPA) that can assist students in understanding the material on the Diversity of Living Creatures in the Environment. This study uses the ADDIE Research method (Analysis, Design, Development, Implementation and Evaluation). The media developed can be declared feasible and valid based on the average score of the language validator who gets a score of 96%, media validator 83% and material validator 96%, results students' understanding of the Diversity of Living Things in the Environment experienced an increase with an average score of 52.35 to 82.35%.